Hubungan Antara Prokrastinasi Akademik Dengan Perilaku Menyontek Pada Siswa SMP - SUMARMO, DWI HARI ADI (2016)
Word "cheating" may be familiar one for students. "Cheating" problem is always found in education world and it is always related to test or examination. One of causes that may induce a cheating behavior is academic procrastination. Purpose of the research is to know relationship between academic procrastination and cheating behavior of secondary school students. Hypothesis of the research is "'Positive correlation is found between academic procrastination and cheating behavior of secondary school students" Variables of the research are academic procrastination and cheating behavior. Population of the research was 7th to 9th students of SMP Negeri 11 Surakarta amounting to 580 individuals consisting of 272 male and 308 female students. Sample was taken from two classrooms, namely VIII-A and VIII-E of the secondary school amounting to 67 students. Data of the research was collected by using academic procrastination scale and cheating behavior scale. The data was analyzed by using product moment correlation. Based on results of discussion, it can be concluded that: 1) a significant positive correlation was found between academic procrastination and cheating behavior of the secondary school's students; 2) the cheating behavior was categorized as moderate level; 3) effective contribution of academic procrastination on the cheating behavior of students was 0.184 or 18.4% meaning that the remaining 81.6% were affected by some other variables on the cheating behavior.